PROFIL FUNGSI KOGNITIF DAN FAKTOR YANG MEMPENGARUHINYA BERDASARKAN KARAKTERISTIK LANSIA DI POSYANDU LANSIA DIKOTO TANGAH - Melya Susanti; Rinita Amelia; Prima Adelin; Rahma Triyana (Yayasan Nusantara Hasana Berdikari, 2024)
The elderly in the world and in Indonesia continue to increase. According to WHO, the number of elderly people worldwide is currently estimated at more than 629 million people, and by 2025 the elderly will reach 1.2 billion. Aging is a process when humans experience a gradual decline in physical/biological, mental and social functions. One of them is a decline in cognitive function. For the elderly, cognitive decline is a major cause of inability to perform normal daily activities, and is also the most common cause of dependence on others for care dependency. Some risk factors for cognitive decline are age, sex, race, genetics, blood pressure, heart failure, arrhythmia, diabetes, lipid and cholesterol levels, thyroid function, obesity, nutrition, alcohol, smoking, and trauma. This study is a descriptive study that aims to assess the profile of cognitive function and the factors that influence it based on the characteristics of the elderly in the elderly posyandu. Risk factors assessed variables assessed are Age, Sex, Blood Pressure, Body mass index, cognitive function. Cognitive function was assessed with MMSE, blood pressure and body mass index taken was assessed directly. The results of this study found that 85% of the elderly were in the age range of 60-74 years. The most elderly gender in this study sample was Women (70%), 50% of the elderly had hypertension. For cognitive function assessment carried out using MMSE and obtained the results of 90% of the elderly have normal cognitive function, 10% experience mild cognitive function decline. BMI in the elderly in this study obtained mixed figures at most normal BMI 55%, 10% underweight, 2% obesity